Polymorphisms of COTL1 gene identified by proteomic approach and their association with autoimmune disorders - Jin, Eun-Heui; Shim, Seung-Cheol; Kim, Hwan-Gyu; Chae, Soo-Cheon; Chung, Hun-Taeg (Experimental & molecular medicine, 2009)
To select candidate genes, we attempted to comparative analysis of protein levels between rheumatoid arthritis (RA) patients and healthy controls by two-dimensional electrophoresis (2-DE) and matrix-assisted laser desorption ionization mass spectrometry (MALDI-TOF-MS). We identified 17 proteins that showed up- or down-regulated spots in RA patients. We found that coactosin-like1 ( COTL1 ) were highly expressed in RA patients compared with healthy controls. We performed a case-control study to determine whether the COTL1 gene polymorphisms were associated with RA and systemic lupus erythematosus (SLE). The genotype frequency of c.-1124G>T and the allelic frequency of c.484G>A in RA patients, and the genotype frequency of c.484G>A in SLE patients were significantly different from healthy controls ( P = 0.009, 0.027, and 0.025, respectively). We also investigated the correlation with the levels of rheumatoid factor (RF) and anti-cyclic citrullinated peptide (CCP) antibody in RA patients, and anti-nuclear antibodies (ANA) in SLE patients. The c.484G>A polymorphism in RA patients has significant association with the levels of anti-CCP antibody ( P = 0.03). Our findings demonstrated that c.-1124G>T and c.484G>A polymorphisms of the COTL1 gene might be associated with the genetic susceptibility of autoimmune disorders.